Solution to navier-stokes equation in stretched coordinate system - Ngali, Mohd Zamani (2005)
Solution to Navier-Stokes equation by Splitting method in physical orthogonal algebraic curvilinear coordinate system, also termed 'stretched coordinate' is presented. The unsteady Navier-Stokes equations with constant density are solved numerically. The linear terms are solved by Crank-Nicholson method while the non-linear term is solved by the second order Adams-Bashforth method. The results show improved in comparison of efficiency and accuracy with benchmark steady solution of driven cavity by Ghia et al. and other first order differencing schemes including splitting scheme in Cartesian coordinate system. Enormous improvements from the original Splitting method in Cartesian coordinate observed where accurate solutions are obtained in minimum 17 X 17 from 33 X 33 resolution for Re = 100, 47 X 47 from 129 X 129 resolution for Re = 400 and 65 X 65 from 259 X 259 resolution for Re = 1000.